Root Cause Analysis and Estimated Time for Completing Administration for Inpatients Discharged from General Hospitals Royal Prima Medan - Winny Wijaya; Chrismis Novalinda Ginting; Sriwahyuni Nasution (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
The discharge process of inpatient care includes activities from when a patient is medically declared fit for discharge until they leave the hospital administratively. This study aims to analyze the root causes and time required for completing inpatient discharge administration at Royal Prima General Hospital Medan. This research used a qualitative analytical approach with a case study design. The informants consisted of 55 people, including 5 hospital staff and 50 patients. Data analysis techniques included data reduction, inductive and deductive analysis, data presentation, and conclusion drawing. The results showed that the average waiting time for inpatient discharge was 53.39 minutes, which is in accordance with the Minimum Service Standards (SPM). However, some units did not meet the standards, particularly the pharmacy department (61.12 minutes). The identified root causes included lengthy administrative procedures, delayed examination reports, limited human resources, drug shortages, and system network issues. In conclusion, although the overall waiting time met the SPM, improvements are needed in pharmacy and administrative units to enhance efficiency and accelerate the discharge process.